2007
DOI: 10.1080/00016480601075399
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis for Bell's palsy: a comparison of diabetic and nondiabetic patients

Abstract: There were no differences in the HB system between the DG and NDG at the start of treatment and at 1 month after onset. However, facial movement in the DG was poorer than that in the NDG at 3 months and 6 months after onset. In terms of the recovery rate, the rate in the DG (52.6%) was much lower than that in the NDG (82.5%) at 6 months after onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 22 publications
1
31
4
1
Order By: Relevance
“…These results were different from the previous studies that showed a beneficial effect of corticosteroids on prognosis in diabetic patients with BP. [14][15][16][17] The discrepancy between our study and the previous studies was possibly due to differences in the study design. In the studies of Kanazawa et al [14] and Akkuzu et al, [15] the comparison was performed between diabetic and non-diabetic BP patients, whereas Riga et al [16] reported the results of steroid therapy for BP within the group of patients who had DM, hypertension, and hyperlipidemia in their study.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…These results were different from the previous studies that showed a beneficial effect of corticosteroids on prognosis in diabetic patients with BP. [14][15][16][17] The discrepancy between our study and the previous studies was possibly due to differences in the study design. In the studies of Kanazawa et al [14] and Akkuzu et al, [15] the comparison was performed between diabetic and non-diabetic BP patients, whereas Riga et al [16] reported the results of steroid therapy for BP within the group of patients who had DM, hypertension, and hyperlipidemia in their study.…”
Section: Discussioncontrasting
confidence: 55%
“…[14][15][16][17] The discrepancy between our study and the previous studies was possibly due to differences in the study design. In the studies of Kanazawa et al [14] and Akkuzu et al, [15] the comparison was performed between diabetic and non-diabetic BP patients, whereas Riga et al [16] reported the results of steroid therapy for BP within the group of patients who had DM, hypertension, and hyperlipidemia in their study. Saito et al [17] had a high cure rate in diabetic patients with the administration of a higher dose steroid regimen than our study.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…High-dose steroids (>120 mg/day of prednisone) have been safely used to treat Bell palsy in patients with diabetes. [23] However, optimal dosing has not been established. Caution should be used in these cases because of the risk of hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%